Pengembangan media pembelajaran menggunakan smart apps creator berbasis discovery learning pada materi Gelombang Bunyi di SMA Kelas XI MIPA - Kartika, Dian Mita; Yanti, Iing Rika; Rahmi, Aidhia (Universitas Ahmad Dahlan, 2024)
Development of learning media Using smart apps creator based on discovery learning on sound wave material in SMA class XI MIPA. This research aims to develop smart application-based learning media using a discovery learning approach in sound wave material for class XI MIPA students in high school. The research method used is research and development (R&D), with procedures based on the ASSURE model and Tessmer's formative evaluation stage. The research subjects included one teacher and 45 students. The research instrument used was a questionnaire to measure the validity and practicality of learning media. The research results show that the learning media developed has a validity level of 85.20% and a practicality level of 88.26%. Thus, it can be concluded that this learning media is valid and practical for high school students in class XI MIPA to study sound waves. The implication of this research is that the developments that have been carried out can provide guidance for learning media developers, encourage the adoption of technology in learning, and motivate teachers to adopt a more interactive and discovery-based learning approach.